(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Рurpose. Upon obtained information from a questionnaire and trial multifocal contact lenses prior operation, our goal is to present a new methodology to select patients for multifocal intraocular correction with an individual definition of the IOL type. Patients and methods. An analysis of 1000 medical case reports (540 hyperopia, 460 myopia) and questionnaire of patients who have undergone operation because of cataract and refractive anomalies in the section of lens surgery and intraocular correction, department of eye diseases in Samara regional clinical hospital named after V. D. Seredavin. Patients are offered monofocal IOLs from leading global manufacturers, such as Rayner, H.Optics and Alcon, bifocal IOLs such as M-plus, Comfort (Oculentis), Restor (Alcon) and the trifocal IOL PanOptix (Alcon) for implantation. To get our goal, questionnaires were developed with questions allowing to determine the psychological type of the patient before the surgery, the nature of his/her visual stress besides requirements and expectations after surgery. Multifocal contact lenses Acuvue Moist with varying ADD power are selected to patients before operation to create similar conditions of multifocal intraocular correction. Visual acuity, contrast sensitivity are evaluated 2 weeks and 2 months postoperatively. At the same time, another survey is conducted to evaluate their satisfaction of visual outcomes. Results. According to analysis, the percentage of implantations of monofocal IOLs was (450 patients) 45%, while percentage of multifocal IOLs was (550 patients ) 55 % among all ultrasound phacoemulsification surgeries. Of these, in (330) 60 % of cases patients have chosen IOLs with a low degree of ADD power (Lentis Comfort), in (165 patients) 30 % — PanOptix and in (55 patients) 10 % — Lentis M-plus or Restor. Degree of satisfaction and visual results in 2 weeks and 2 months was recorded from (5 points) and obtained (506 patients) 92 % and (528 patients) 96 % respectively. Cases with incomplete patient dissatisfaction don’t exceed (18 patients) 3.2 % and is reported mainly in the group with the implantation of bifocal IOLs and are related with typical complaints of light phenomena, mostly at night.